Individual predictors of COVID-19 disinformation detection and sharing via WhatsApp - Brenes Peralta, Carlos Manuel (2024)
This study examines cognitive, socio-political, and socio-demogra-phic predictors of the evaluation and willingness to share disinformation about COVID-19 via WhatsApp. Using an online survey, a convenience sample of 553 Costa Rican adults were exposed to disinformation about vaccines and the state’s response to the pandemic. Results show that peo-ple who support authoritarian, conservative and pro-state ideologies, and those with low reflective thinking, were more likely to believe and share disinformation. Moreover, among people with low reflective thinking, older people were more likely to detect disinformation. Finally, highly religious individuals and younger conservatives with lower education expressed more willingness to share disinformation.